Behavioral Design: A New Approach to Development Policy. (March 2014) - Datta, Saugato; Mullainathan, Sendhil; Jäntti, Markus; Kanbur, Ravi; Pirttilä, Jukka
<x xml:space="preserve">Abstract</x> Successful development programs rely on people to behave and choose in certain ways, and behavioral economics helps us understand why people behave and choose as they do. This paper sketches how to design development programs and policies in ways that are cognizant of and informed by the insights behavioral economics provides into human behavior. It distills the key insights of behavioral economics into a parsimonious framework about the constraints under which people make decisions. It then shows how this framework leads to a set of design principles that can be employed to design programs in areas including health, education, productivity, agriculture, finance, and the delivery of public services. Finally, it offers some reflections on the ways in which these insights and design principles can be incorporated into existing and planned programs to improve their reach and effectiveness.